Considerations for Germline Testing in Melanoma: Updates in Behavioral Change and Pancreatic Surveillance for Carriers of CDKN2A Pathogenic Variants - Pauley, Kristen; Khan, Ambreen; Kohlmann, Wendy; Jeter, Joanne (Frontiers in Oncology, 2022)
The largest proportion of hereditary melanoma cases are due to pathogenic variants (PVs) in the CDKN2A/p16 gene, which account for 20%-25% of familial melanomas and confer up to a 30%-70% lifetime risk for melanoma in individuals with these variants. In addition, PVs in the CDKN2A gene also increase risk for pancreatic cancer (~5–24% lifetime risk). Individuals with PVs in the CDKN2A gene also tend to have an earlier onset of cancer. Despite these known risks, uptake of germline testing has been limited in the past, largely due to perceptions of limited benefit for patients. Prevention recommendations have been developed for individuals with CDKN2A PVs as well the providers who care for them. On the patient level, behavioral modifications regarding melanoma prevention such as wearing sunscreen, limiting prolonged sun exposure and practicing general sun safety can help reduce risks. Germline testing can provide motivation for some individuals to adhere to these lifestyle changes. On the provider level, pancreatic cancer surveillance for individuals with CDKN2A PVs has been increasingly endorsed by expert consensus, although the efficacy of these surveillance methods remains under study. This review summarizes the updated surveillance guidelines for individuals with CDKN2A PVs and explores the impact of genetic counseling and testing in influencing behavioral changes in these individuals.